2009
DOI: 10.1093/intimm/dxp121
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TOSO/FAIM3 as an Fc receptor for IgM

Abstract: Fc receptors specifically bind to the Fc region of Igs to mediate the unique functions to each class of Igs. To identify a novel Fc receptor for IgM, we searched expressed sequence tag database for molecules containing Ig domains with homology to those of known Fc receptors for IgM, Fcalpha/muR and polymeric Ig receptor. As a result, we identified TOSO/Fas apoptotic inhibitory molecule 3 (FAIM3) as a possible Fc receptor for IgM. HeLa cells transfected with a TOSO/FAIM3-expression vector bound to IgM but not I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 32 publications
3
94
0
1
Order By: Relevance
“…These results reveal a critical role for FcμR in B-cell survival following antigen stimulation and humoral immune responses. One unique feature of FcμR is its specific expression on B cells in mice, as shown by FACS analysis in our previous (17) and current studies. Consistently, microarray analysis revealed that Fcmr transcripts were only detectable in isolated B cells, as well as in spleen and lymph node tissues, but not in any other mouse tissues or cell types examined.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These results reveal a critical role for FcμR in B-cell survival following antigen stimulation and humoral immune responses. One unique feature of FcμR is its specific expression on B cells in mice, as shown by FACS analysis in our previous (17) and current studies. Consistently, microarray analysis revealed that Fcmr transcripts were only detectable in isolated B cells, as well as in spleen and lymph node tissues, but not in any other mouse tissues or cell types examined.…”
Section: Discussionsupporting
confidence: 69%
“…Our previous studies revealed that FcμR was expressed in B cells but not in T cells, dendritic cells, and macrophages in mice (17). We further analyzed FcμR expression during B-cell development, maturation, and activation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, the role of IgM might be linked to its binding to a putative Fc receptor (47)(48)(49) or perhaps attributable to simple aggregation of the Ag, thereby making it more immunogenic. Moreover, mice lacking secretory IgM have developmental defects in their B-cell compartment secondary to the lack of secretory IgM, and it is conceivable that this explains their impaired Ab responses (37,50).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since monomeric IgM is the only virgin B-cell receptor in swine, pigs lacking IgD [39], IgM cleavage might inhibit B-cell activation and thus have far reaching consequences for cell mediated immunity. It has been shown that FcµR, expressed on B-lymphocytes, is an uptake receptor for IgM labeled pathogens [40]. It is therefore reasonable to assume that cleavage of IgM bound to the bacterial surface might hinder uptake of IgM labeled bacteria by B-lymphocytes and thus encumber their antigen presenting ability.…”
Section: Discussionmentioning
confidence: 99%